Effect of thermal aging on microstructure and microhardness of AL–12SI–4MG alloy containing cerium - Anasyida, Abu Seman; Abdul Razak, Daud; Mariyam Jameelah, Ghazali (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.